Board Diversity, Managerial Ownership, and Information Transparency on Company Value in Indonesian Public listed Companies: Studi Kasus: Perusahaan Sektor Consumer Non-Cyclical yang Terdaftar di BEI tahun 2017-2021 - Leny Suzan; Dara Rahma Septia - (Universitas Medan Area, 2023)
Company values have an important role and need to be the main concern for a company. This is because the value of the company has an important contribution to shareholders, along with the increase in share price. Through signaling theory that is used by several companies in the process of conveying information about the value of the company to investors by utilizing certain signals. The research conducted aims to identify the impact of board diversity, managerial ownership, and transparency of information carried out partially and simultaneously for the value of a company. In this case, researchers utilize secondary data on the IDX (Indonesia Stock Exchange). The research population in the form of non-cyclical consumer companies was listed on the Indonesia Stock Exchange for the 2017-2021 period, with a total of 15 companies being sampled. The sampling process utilizes purposive sampling techniques. The study utilized regression analysis techniques on panel data by utilizing Eviews 12 software. The results shown are board diversity, managerial ownership, and information transparency have a simultaneous impact on the value of a company. Based on the partial aspect, board diversity has an important effect on the value of a company. However, managerial ownership and transparency of information have no impact for the company.